And to think that I saw it on Mulberry Street - Seuss, Dr. (New York : Random House, 1989)
A boy imagines a series of incredible sights on his way home from school so that he will have an interesting report to give his father.
"A Vanguard Press book.".
"Originally published in 1937 by Vanguard Press"--T.p. verso.
Elem. School Library Collection.
Library Journal.
Wilson's Children.
3.2.
Keywords: Imagination -- Fiction; Stories in rhyme; Imagination -- Fiction; Nonsense verses; Stories in rhyme